Novel fluorescence resonance energy transfer‐based reporter reveals differential calcineurin activation in neonatal and adult cardiomyocytes. (22nd July 2015) - Bazzazi, Hojjat; Sang, Lingjie; Dick, Ivy E.; Joshi‐Mukherjee, Rosy; Yang, Wanjun; Yue, David T.
Abstract : Key points: Novel fluorescence resonance energy transfer‐based genetically encoded reporters of calcineurin are constructed by fusing the two subunits of calcineurin with P2A‐based linkers retaining the expected native conformation of calcineurin. Calcineurin reporters display robust responses to calcium transients in HEK293 cells. The sensor responses are correlated with NFATc1 translocation dynamics in HEK293 cells. The sensors are uniformly distributed in neonatal myocytes and respond efficiently to single electrically evoked calcium transients and show cumulative activation at frequencies of 0.5 and 1 Hz. In adult myocytes, the calcineurin sensors appear to be localized to the cardiac z‐lines, and respond to cumulative calcium transients at frequencies of 0.5 and 1 Hz. Abstract: The phosphatase calcineurin is a central component of many calcium signalling pathways, relaying calcium signals from the plasma membrane to the nucleus. It has critical functions in a multitude of systems, including immune, cardiac and neuronal. Given the widespread importance of calcineurin in both normal and pathological conditions, new tools that elucidate the spatiotemporal dynamics of calcineurin activity would be invaluable. Here we develop two separate genetically encoded fluorescence resonance energy transfer (FRET)‐based sensors of calcineurin activation, DuoCaN and UniCaN. Both sensors showcase a large dynamic range and rapid response kinetics, differing primarily in the linker structure between the FRET pairs. Both sensors were calibrated in HEK293 cells and their responses correlated well with NFAT translocation to the nucleus, validating the biological relevance of the sensor readout. The sensors were subsequently expressed in neonatal rat ventricular myocytes and acutely isolated adult guinea pig ventricular myocytes. Both sensors demonstrated robust responses in myocytes and revealed kinetic differences in calcineurin activation during changes in pacing rate for neonatal versus adult myocytes. Finally, mathematical modelling combined with quantitative FRET measurements provided novel insights into the kinetics and integration of calcineurin activation in response to myocyte Ca transients. In all, DuoCaN and UniCaN stand as valuable new tools for understanding the role of calcineurin in normal and pathological signalling. Abstract :